Reciprocal modeling of university students' perceptions of the learning environment, engagement, and learning outcome: A longitudinal study. (February 2023) - Guo, Jian-Peng; Lv, Shuai; Wang, Shi-Chao; Wei, Si-Mei; Guo, Yi-Rong; Yang, Ling-Yan
Abstract: While researchers have proposed a reciprocal and bidirectional relationship among students' perceptions of their learning environment, engagement, and learning outcomes in college learning, scant research has effectively tested this assertion using longitudinal data. The present study examined this relationship with the use of an auto-/cross-lagged longitudinal structural equation modelling across a lag of 2.5 years. University students' ( N  = 966) perceptions of the learning environment, engagement, generic skills, and GPA were surveyed and collected at sophomore and senior years. In addition to significant auto-lagged effects, the cross-lagged results showed unidirectional predicting paths from prior perceptions to subsequent engagement, and reciprocal and bidirectional relationship between engagement and generic skills. The results provided partial support for the reciprocity of these variables, and confirmed the important role of engagement in the process of college student learning, which extends previous cross-sectional findings in theoretical meaningful ways. Highlights: Longitudinally test the reciprocity of perceptions, engagement, and outcomes. The auto-lagged effects were much stronger than the cross-lagged effects. Significant reciprocal relation between engagement and generic skills was found. Important role of engagement in the process of college learning was confirmed. Academic achievement and other variables were developmentally independent.